The Relationship Between Knowledge and Attitude About Anemia with Compliance to Consume Iron Supplement Tablets in Female Adolescents of Grade X at State Senior High School 13 Surabaya - Ainur Wachidah Choirun Niza; Annas Buanasita; Mujayanto; Riezky Faisal Nugroho; Fahmi Hafid; Sharifah Intan Zainun Sharif Ishak (Politeknik Kesehatan Kemenkes Surabaya, 2024)
The transition from childhood to adulthood that adolescents go through is known as the